Iqra Era 5.0: Belajar Tanpa Batas dan Transformasi Ilmu di Era Digital (Al-‘Alaq Ayat 1-5) - Eni Setiawati; Serly Oktavianti; Utami Widia Putri (STIKes Ibnu Sina Ajibarang, 2025)
Surah Al-‘Alaq verses 1–5 as theological and philosophical foundations for the development of science, especially in facing the transformation of education in the digital era. The early verses of this revelation emphasize the importance of reading, learning, and seeking knowledge with spiritual awareness, as a form of obedience to Allah SWT. The research method used is library research, by examining classical and contemporary interpretations and relevant literature on technology and Islamic education. The results of the study show that the main message of Surah Al-‘Alaq is very relevant to modern challenges, where the development of information technology and artificial intelligence (AI) is changing the way humans acquire and disseminate knowledge. However, Islam emphasizes that knowledge must be used responsibly, ethically, and for the benefit of the community. Therefore, digital learning from an Islamic perspective must remain based on spiritual values, prophetic ethics, and an orientation towards the benefits of knowledge. The integration of revelation and technology is key to creating a transformative and character-based education system in the digital era.